Innovative Model of Tiered Early Childhood Education (ECE) Training: A Case Study of the West Sumbawa Regency Education and Culture Office - Armiaty; Khadafie, Muammar (Manunggal Halim Jaya, 2025)
This research investigates the implementation of tiered training programs for early childhood education (PAUD) teachers and their effectiveness in enhancing professional competence. Employing a qualitative case study design, the study provides an in-depth analysis of how such training influences teachers' academic qualifications, particularly in the domains of knowledge, pedagogical skills, and professional attitudes. The findings reveal that the tiered training approach significantly contributes to the development of teachers' capacities by addressing their practical needs in the classroom. Teachers reported substantial benefits, including improved understanding of child development, the ability to design innovative lesson plans (RPP), and the application of effective and contextualized learning strategies. Furthermore, the incorporation of innovative training methods such as case studies, simulations, and the integration of digital technologies ensures that the training remains both relevant and applicable to contemporary educational contexts. Overall, the study concludes that the innovation embedded in the tiered training program has been systematically and strategically designed, resulting in measurable improvements in teachers' performance and professional growth. These outcomes underscore the critical role of structured capacity-building initiatives in advancing the quality of early childhood education.